It's not just about 'more': A research project exploring satisfaction with opportunities to play, for children in two Welsh neighbouring communities. Issue 1 (2nd January 2017) - Long, Alexandra
ABSTRACT: This paper discusses a research project undertaken during spring 2014, in response to the findings of the Play Sufficiency Assessment in one Welsh Local Authority. The results highlighted anomalous findings between two neighbouring communities regarding the children's self-reported levels of satisfaction with opportunities to play. The research study aimed to identify factors which may have caused the disparity in satisfaction between the two communities. The findings of the research indicate that simply having more places to play is not automatically an indicator of satisfaction. Factors such as child and parental fear, socio-economic conditions and the development of a 'play culture' within communities have a more significant role in influencing children's freedom and opportunities to play.